Surgical Management of Unusual Biangular Mandibular Fractures - Stefan Cocis; Umberto Autorino; Fabio Roccia; Chiara Corio (Case Reports in Surgery)
Bilateral mandibular angle fractures, while representing a rarity among mandibular fractures, are a huge challenge of complex management for the maxillofacial surgeon. There are still many open questions regarding the ideal management of such fractures, including the following: the removal of the third molar in the fracture line, the best surgical approach, and the fixation methods. In this report the authors present the case of 40-year-old man presenting with a bilateral mandibular angle fracture referred to the Maxillofacial Surgery Department of Turin. Open reduction and internal fixation has been made for both sides. The left side third molar was removed and the internal fixation was achieved through internal fixation with one miniplate according to Champy’s technique and transbuccal access for a 4-hole miniplate at the inferior border of the mandible. Right side third molar was not removed and fixation was achieved through intraoral access and positioning of a 4-hole miniplate along the external ridge according to Champy. An optimal reduction was achieved and a correct occlusion has been restored.